PENGEMBANGAN BAHAN AJAR BERBASIS KONTEKSTUAL PADA MATERI HIMPUNAN BERBANTU VIDEO PEMBELAJARAN - Yulis Purwanto; Swaditya Rizki (UNIVERSITAS MUHAMMADIYAH METRO, 2015)
The objective of this research was to know the feasibility of mathematics contextual-based learning materials on the material set using video-assisted learning. This research was a research and development (R & D). Models were used to adapt the model developed by Sugiyono, but not to stage a mass product. Subjects tested in this study was seventh grade Junior high school 1 Batanghari academic year 2014/2015. Results of the validation of teaching materials to obtain an average value of 82.14%. Learning outcomes of the pilot study of small-scale was 84 and learning outcomes of large-scale was 84.33, so the contextual-based learning materials on the material set using video-assisted learning was very feasible used in learning